Unraveling the 17β-Estradiol Degradation Pathway in Novosphingobium tardaugens NBRC 16725 - Ibero, Juan; Galán, Beatriz; Rivero-Buceta, Virginia; García, José L. (Frontiers in Microbiology, 2020)
We have analysed the catabolism of estrogens in Novosphingobium tardaugens NBRC 16725, that is able to use endocrine disruptors such as 17-estradiol, estrone and estriol as sole carbon and energy sources. A transcriptomic analysis enabled the identification of a cluster of catabolic genes (edc cluster) organized in two divergent operons that are involved in estrogen degradation. We have developed genetic tools for this estrogen-degrading bacterium, allowing us to delete by site directed mutagenesis some of the genes of edc cluster and complement them by using expression plasmids to better characterize their precise role in the estrogen catabolism. Based on these results a catabolic pathway is proposed. The first enzyme of the pathway (17β-hydroxysteroid dehydrogenase) used to transform 17-estradiol into estrone is encoded out of the cluster. A CYP450 encoded by edcA gene performs the second metabolic step, i.e., the 4-hydroxylation of estrone in this strain. The edcB gene encodes a 4-hydroxyestrone-4,5-dioxygenase that opens ring A after 4-hydroxylation. The initial steps of the catabolism of estrogens and cholate proceed through different pathways. However, the degradation of estrogens converge with the degradation of testosterone in the final steps of the lower catabolic pathway used to degrade the common intermediate 3aα-H-4α(3′-propanoate)7a-β-methylhexahydro-1,5-indanedione (HIP). The TonB dependent receptor protein EdcT appears to be involved in estrogen uptake, being the first time that this kind of proteins have been involved in steroid transport.